2015
DOI: 10.1007/s11682-015-9388-2
|View full text |Cite
|
Sign up to set email alerts
|

White and grey matter relations to simple, choice, and cognitive reaction time in spina bifida

Abstract: Elevated reaction time (RT) is common in brain disorders. We studied three forms of RT in a neurodevelopmental disorder, spina bifida myelomeningocele (SBM), characterized by regional alterations of both white and grey matter, and typically developing individuals aged 8 to 48 years, in order to establish the nature of the lifespan-relations of RT and brain variables. Cognitive accuracy and RT speed and variability were all impaired in SBM relative to the typically developing group, but the most important effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 49 publications
(53 reference statements)
3
14
0
Order By: Relevance
“…As expected from our previous findings, the adults with SBM exhibited parallel deterioration of cognitive control abilities to that in normal aging (Dennis et al, 2015; Treble-Barna et al, 2015). With the exception of performance accuracy during the WMST, none of the group by age interactions significantly related to cognitive performance.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…As expected from our previous findings, the adults with SBM exhibited parallel deterioration of cognitive control abilities to that in normal aging (Dennis et al, 2015; Treble-Barna et al, 2015). With the exception of performance accuracy during the WMST, none of the group by age interactions significantly related to cognitive performance.…”
Section: Discussionsupporting
confidence: 89%
“…This has lead to the formulation of a modal profile of cognitive processing in SBM that includes relatively spared associative processing abilities, such as the activation and categorization of information related to stimuli that is based on formed associations, and relatively disrupted assembled processing or integration of information, particularly to exogenous stimuli. Although the conceptualization of this profile is predominantly based on studies of younger individuals and youth, the two known studies of adults with SBM supported assembled processing deficits of impaired prospective and verbal episodic memory and response (processing) speed (Dennis et al, 2015; Treble-Barna et al, 2015). In the current study, difficulty responding to learned associations of visually presented stimuli supported deficient capacity for maintaining information of exogenous stimuli in the adults with SBM.…”
Section: Discussionmentioning
confidence: 99%
“…8 There are few studies of the default mode network and pertinent related networks in adolescents and young adults born very preterm or with myelomeningoceles. 3,4,10 But current results demonstrate that these patients have abnormal networks. 3,4,10 Pediatric neurosurgeons need to advocate for more research about shunt-dependent hydrocephalus to understand the relevant pathophysiology and to develop interventions specific for patients with this condition.…”
mentioning
confidence: 51%
“…3,4,10 But current results demonstrate that these patients have abnormal networks. 3,4,10 Pediatric neurosurgeons need to advocate for more research about shunt-dependent hydrocephalus to understand the relevant pathophysiology and to develop interventions specific for patients with this condition. Currently, very few evidencebased recommendations are available to treat chronic headaches in patients with congenital brain abnormalities, including those with shunted hydrocephalus.…”
mentioning
confidence: 51%
“…Processing speed tasks are often used in studies of academic skills (Shanahan et al, 2006); there is evidence that RT and processing speed measures are significantly correlated with one another, and that more complex measures show stronger relations with academic achievement (Buckhalt, 1991;Catts, Gillispie, Leonard, Kail, & Miller, 2002). A recent crosssectional study of RT (Dennis et al, 2016) used a wide age range (ages 8 to 40) and found that, despite slowed RTs relative to TD controls, individuals with SBM exhibited similar (complex quadratic) relations between RT and age, showing rapid decreases through childhood/adolescence, with slower rises through adulthood. What has not been studied is how other neurocognitive domains predict academic fluency outcomes when RT for non-academic stimuli is included in the models.…”
Section: Development Of Academic Fluency In Td and Sbm Individualsmentioning
confidence: 99%